EVALUASI SISTEM PELAYANAN TRANSIT ANTAR KORIDOR BUS RAPID TRANSIT TRANS SEMARANG - Salasa, Wildan; Wakhidho, Heru; Setiadji, Bagus Hario; Yulipriyono, Epf. Eko (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Trans Semarang transit happens at, semarang 5 public high school shelter, town hall shelter, simpang lima shelter, tawang station shelter and Elizabeth hospital shelter. The lowest headway analyst result 52 second in the Elisabeth and Simpang Lima, and the highest headway BRT Trans Semarang is 40 minutes in the Station Tawang, should to the ideal headway at 5-10 minutes. Lowest idle time is 35 second in the SMAN 5 and Station Tawang, and highest idle time BRT Trans Semarang is 68 second in the Station Tawang and Simpang Lima, should between 20-60 second. The lowest waiting time is at 52 seond in the Simpang Lima, and the highest waiting time BRT Trans Semarang is 35 minutes in the Station Tawang, should between 5-10 minutes and maksimum 10-20 minutes, and the shelter facilities are considered enough by the BRT Trans Semarang users.